Analisis Potensi Sektor Ekonomi Kabupaten Bengkayang Tahun 2018-2022 (Pendekatan Shift Share dan Typologi Klassen) - Reo Zaputra (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
Inequality in economic growth between sectors is one of the main obstacles faced in regional development, including in Bengkayang Regency, West Kalimantan. This regency has significant natural resource wealth, but its utilization is still uneven in supporting sustainable economic growth. This study aims to evaluate the potential of the economic sector in Bengkayang Regency during the 2018-2022 period by applying the Shift Share method and Klassen Typology. The Shift Share method is applied to evaluate the effect of national economic growth on economic sectors in Bengkayang Regency, identifying components of national growth, sector proportions, and sectoral competitiveness. Meanwhile, the Klassen Typology is used to group economic sectors based on their contribution to the economy and their growth rate into four quadrant categories. This study uses data on the Gross Regional Domestic Product (GRDP) of Bengkayang Regency for the 2018-2022 period based on constant prices. The research findings indicate that the agriculture, forestry, and fisheries sectors are the mainstay sectors in quadrant 1 (advanced sectors with rapid growth), showing more prominent growth compared to other sectors. Meanwhile, sectors such as financial services, manufacturing, and transportation and warehousing are categorized in quadrant 4 (relatively lagging sectors) requiring special attention for further development.